Analisis faktor-faktor yang mempengaruhi price earning ratio pada perusahaan manufaktur yang bursa efek indonesia 2007-2011terdaftar di - Ramadhani, Gesha; Silfi, Alfiati; ', Kamaliah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The stock market is an indicator of the progress of a country's economyand to support economic development the country concerned. Various role of capital markets in a country that is as a facility to do the interaction between buyer and seller to determine the stock price. one analysis tool in the assessment of the stock price is Price Earning Ratio (PER). This study aims to examine the factors DER, ROE, PBV and Size of Price Earning Ratio (PER) on manufacturing companies listed in Indonesia Stock Exchange for 2007 - 2011.This study used the entire population of manufacturing companies listed in Indonesia Stock Exchange (BEI) in 2007 until 2011, a total of 33 companies. Sampling was conducted with a purposive sampling technique. This study uses secondary data obtained from the publication of Indonesian Capital Market Directory (ICMD). The analysis technique used in this study is the technique of multiple linier regression analysis, Goodness of Fit Test and using the t-statistic for testing the partial regression coefficient with the 5% confidence level.In the classical assumption test results showed that there were nodeviations classical assumption, this shows that the available data has been qualified to use multiple linier regression model. From this reseach the following conclusion : the DER variable has positive and significant effect on PER, variabel ROE has negative and significant effect on PER, PBV variable has positive and significant effect on PER, Size variable has not significant effect on PER. Regression equation obtained is PER = 7,405 + 1,178 DER – 4,240 ROE + 2,414 PBV + 0,022 SIZE. Coefficient of determination (adjusted 2) is 16,0 % which means 16,0 % of PER is influenced by the independent variables, whereas the remaining balance of 84,0% is explained by other variable not prensented in the study.Keywords : Price Earning Ratio (PER), Debt To Equity Ratio (DER), Return On Equity (ROE), Price Book Value (PBV) dan Size